Intrabolus pressure on high-resolution manometry distinguishes fibrostenotic and inflammatory phenotypes of eosinophilic esophagitis. Issue 6 (1st September 2016) - Colizzo, J. M.; Clayton, S. B.; Richter, J. E.
Summary: The aim of this investigation was to determine the motility patterns of inflammatory and fibrostenotic phenotypes of eosinophilic esophagitis (EoE) utilizing high-resolution manometry (HRM). Twenty-nine patients with a confirmed diagnosis of EoE according to clinicopathological criteria currently being managed at the Joy McCann Culverhouse Swallowing Center at the University of South Florida were included in the retrospective analysis. Only patients who completed HRM studies were included in the analysis. Patients were classified into inflammatory or fibrostenotic subtypes based on baseline endoscopic evidence. Their baseline HRM studies prior to therapy were analyzed. Manometric data including distal contractile integral, integrated relaxation pressure, and intrabolus pressure (IBP) values were recorded. HRM results were interpreted according to the Chicago Classification system. Statistical analysis was performed with SPSS software (Version 22, IBM Co., Armonk, NY, USA). Data were compared utilizing Student's t -test, χ 2 test, Pearson correlation, and Spearman correlation tests. Statistical significance was set at P < 0.05. A total of 29 patients with EoE were included into the retrospective analysis. The overall average age among patients was 40 years. Male patients comprised 62% of the overall population. Both groups were similar in age, gender, and overall clinical presentation. Seventeen patients (58%) had fibrostenotic disease, and 12 (42%) displayed inflammatory disease. The average IBP for the fibrostenotic and inflammatory groups were 18.6 ± 6.0 mmHg and 12.6 ± 3.5 mmHg, respectively ( P < 0.05). Strictures were only seen in the fibrostenotic group. Of the fibrostenotic group, 6 (35%) demonstrated proximal esophageal strictures, 7 (41%) had distal strictures, 3 (18%) had mid-esophageal strictures, and 1 (6%) patient had pan-esophageal strictures. There was no statistically significant correlation between the level of esophageal stricture and degree of IBP. Integrated relaxation pressure, distal contractile integral, and other HRM metrics did not demonstrate statistical significance between the two subtypes. There also appeared no statistically significant correlation between patient demographics and esophageal metrics. Patients with the fibrostenotic phenotype of EoE demonstrated an IBP that was significantly higher than that of the inflammatory group.